A kinetics-based universal model for single bubble growth and departure in nucleate pool boiling. (August 2018) - Haustein, Herman D.
Highlights: An analytical/empirical study on the coupled bubble growth and departure combining a traditional macro analysis with a micro-scale viewpoint. An extensive discussion of the most suitable form of heat transfer and drag coefficients for a bubble growing near a wall. Identification of the importance of the kinetic parameter, L/RT, and a new regime map based on it. A new explanation to additional pressure dependence of bubble departure, and trend transition in bubble growth/departure at high pressures. A new universal model covering 19 different liquids, a wide range of pressures, micro to macro departing bubbles and a range of gravity levels. Abstract: A suitable universal model for boiling heat transfer has been pursued for a very long time. The present work is a significant step towards such a model by dealing with the inherent bubble dynamics. As in previous works the bubble growth and departure are shown to be coupled and are dealt with simultaneously. For departure, the force balance is relatively straightforward, depending on a suitable drag coefficient. However, for growth the thermal aspects and boiling dynamics are rather more complicated. The present study not only draws from a 1D energy balance, but explains the need for correction of the effective superheat, based on kinetic theory and consideration of the vapor Knudsen layer conditions (following Ytrehus and Ostmo, 1996). Thereby, the present study merges a traditional macro approach with a micro, near-interface viewpoint, thereby identifying L /ℜT as the most significant parameter, besides the superheat (Jakob number). This approach provides a new explanation for the additional pressure dependence found in bubble departure, and the transition in trend at high pressure. The present study also extends the range typically considered, to include 19 liquids/liquefied gases, up to near critical pressures, sub-millimeter to several centimeter bubbles and gravity levels down to 1/16th that of earth, providing good prediction over the entire range. This range is limited at the one end by the dominance of micro-layer evaporation and substrate conduction at lower superheats, and at the other by bubble interaction - thermal robbing and bubble coalescence.